Application of early language teaching methodology in digital education. A research project by the hungarian academy of sciences and the faculty of primary and preschool education, Eötvös Loránd University - Árva Valéria; Márkus Éva; Trentinné Benkő Éva (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The following paper is an interim report of the research project carried out by the Childhood Digital Language Teaching Research Group, consisting of members of the Department of Foreign Languages and Literature at the Faculty of Primary and Preschool Education, Eötvös Loránd University (ELTE TÓK). The group was established in response to the call Research Programme for Public Education Development by the Hungarian Academy of Sciences. The research investigates the effects of emergency online teaching on the subsequent classroom practices of primary language teachers. The leader of the research group is Professor Emeritus Péter Medgyes (MTA.ELTE.TOK.idegennyelv@tok.elte.hu).
A gyermekkori nyelvtanítás módszertanának alkalmazása digitális oktatásban. Az MTA és az ELTE TÓK kutatási projektje
Keywords: language teaching; online education; questionnaire; coronavirus (Covid); best practices